Presidential Decree-Law No. 52 of the Year 2014 Amending Some Provisions of the Law on the Regulation of Universities, As Promulgated by Law No. 49 of the Year 1972 = قرار رئيس جمهورية مصر العربية بالقانون رقم 52 لسنة 2014 بتعديل بعض أحكام قانون تنظيم الجامعات الصادر بالقانون رقم 49 لسنة 1972 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.